2002
DOI: 10.1046/j.1432-1033.2002.03040.x
|View full text |Cite
|
Sign up to set email alerts
|

Substrate selectivity and sensitivity to inhibition by FK506 and cyclosporin A of calcineurin heterodimers composed of the α or β catalytic subunit

Abstract: The calcineurin (CaN) a and b catalytic subunit isoforms are coexpressed within almost all cell types. The enzymatic properties of CaN heterodimers comprised of the regulatory B subunit (CnB) with either the a or b catalytic subunit were compared using in vitro phosphatase assays. CaN containing the a isoform (CnAa) has lower K m and higher V max values than CaN containing the b isoform (CnAb) toward the PO 4 -RII, PO 4 -DARPP-32(20-38) peptides, and p-nitrophenylphosphate (pNPP). CaN heterodimers containing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 45 publications
0
52
0
Order By: Relevance
“…In addition, targeted gene knockouts in mice of ␣ or ␤ forms of the CaNA subunit revealed different roles in the cell physiology of muscle cells (␤ [9]) and hippocampus cells (␣ [100]). Finally, biochemical studies on the CaNA-␣ and -␤ isoforms in humans have shown that the two isoforms display substrate specific differences in their sensitivity to known inhibitors of calcineurin activity (71), providing a biochemical basis for isoform differences in function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, targeted gene knockouts in mice of ␣ or ␤ forms of the CaNA subunit revealed different roles in the cell physiology of muscle cells (␤ [9]) and hippocampus cells (␣ [100]). Finally, biochemical studies on the CaNA-␣ and -␤ isoforms in humans have shown that the two isoforms display substrate specific differences in their sensitivity to known inhibitors of calcineurin activity (71), providing a biochemical basis for isoform differences in function.…”
Section: Discussionmentioning
confidence: 99%
“…In the heart, each isoform comprises approximately 50% of the total catalytic isoform expression (8), although calcineurin A␤ protein levels increase during hypertrophy while A␣ levels remain unchanged (45). At the biochemical level, calcineurin A␣ and A␤ differ slightly in their enzymatic properties such that A␣ has a lower K m and a higher V max toward the phosphorylated RII peptide than does A␤ (35). While calcineurin A␣ and A␤ each show identical calmodulin dissociation rates and similar inhibition curves to the autoinhibitory peptide, the A␣ isoform is more sensitive to FK506 inhibition than is A␤ (35).…”
Section: Discussionmentioning
confidence: 99%
“…At the biochemical level, calcineurin A␣ and A␤ differ slightly in their enzymatic properties such that A␣ has a lower K m and a higher V max toward the phosphorylated RII peptide than does A␤ (35). While calcineurin A␣ and A␤ each show identical calmodulin dissociation rates and similar inhibition curves to the autoinhibitory peptide, the A␣ isoform is more sensitive to FK506 inhibition than is A␤ (35). Collectively, these previous reports indicate that calcineurin A␣ and A␤ are subject to different levels of regulation in multiple tissues and that each has slightly different biochemical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin (Cn) 3 , a heterodimeric serine/threonine phosphatase enzyme, is the only protein phosphatase dependent on Ca 2ϩ . The enzyme is composed of an A subunit and a B subunit.…”
Section: © 2011 American Association For Clinical Chemistrymentioning
confidence: 99%
“…The other isoforms appear in all tissues, albeit in varying ratios (2 ). These isoforms differ quite extensively in their enzyme kinetics and physiological functions (3,4 ). For instance, lack of CnA␤, the predominant isoform in lymphocytes, leads to inadequate T-cell development and a compromised immune response in mice (5 ).…”
Section: © 2011 American Association For Clinical Chemistrymentioning
confidence: 99%